NOT ANOTHER CASE OF JUVENILE IDIOPATHIC ARTHRITIS: CONGENITAL INSENSITIVITY TO PAIN PRESENTING WITH JOINT PROBLEMS - Sadia Khurshid; Khursheed, Tayyeba; Muhammad Sufyan Khan (Journal of Ayub Medical College Abbottabad, 2021)
Congenital insensitivity to pain with anhidrosis (CIPA) is a rare condition with protean manifestations. Occasionally, these diseases may present with musculoskeletal problems. Here we report a case of young child who presented with joint problems in our clinic. Since the child had a number of musculoskeletal manifestations her diagnosis was difficult and delayed. She was given supportive treatment and a team of doctors from different specialties was involved in her management.